Komunikasi Inovasi Studi Implementasi Aplikasi I-Pubers (Integrasi Pupuk Bersubsidi) - Sulis, Sulis; Ayuningtyas, Fitria; Muqsith, Munadhil Abdul (Jurnal Media dan Komunikasi Indonesia, 2024)
In support of SDGs program no. 2 Zero Hunger, the fulfillment of food supply, especially the availability of rice for national food, must be considered. The government through Kementerian Pertanian RI  with Kementerian Badan Usaha Milik Negara (BUMN) appointed PT Pupuk Indonesia and released an application, namely the integration of Pupuk Bersubdi (i-Pubers). Launching i-Pubers is a form of communication of innovations from government programs. The acceptance of the application is a TAM model with an innovation diffusion approach so that i-Pubers can answer the needs of farmers about the effective and efficient redemption process of subsidized fertilizers. The purpose of this study is to describe and explain the implementation of the TAM model innovation in the i-Pubers application in the subsidized fertilizer redemption process. This research uses a qualitative research method with descriptive analysis, while the data collection method is through interviews, document studies, and observations with informants of a partner owners, farmers, and farmer. The results of the research with these informants show that the Barito Kuala community consisting of Farmers, Agricultural Extension Officers, and Subsidised Fertiliser Kiosk Owners or Kiosk Partners are coils that each other has a role to succeed in using i-Pubers. Community acceptance of the i-Pubers application is a form of acceptance because the application is easy and useful in supporting fertilizer needs in Barito Kuala Regency.